GAMBARAN MOTIVASI BERPRESTASI DAN FREKUENSI LATIHAN PADA MASA PANDEMI - Susanto, Indra Himawan (Universitas Negeri Surabaya, 2022)
Sports achievement motivation is a goal or a means of driving athletes to achieve the expected goals, such as achievement. The purpose of this study was to determine and describe the achievement motivation and frequency of athletes' training during the pandemic. The research method used in this research is descriptive qualitative research using a research instrument in the form of a questionnaire. The results of this study are that the frequency of student training during this pandemic to keep achieving is 20.3% training 3 times and 6 times a week, while for the category of achievement motivation it is 68% and belongs to the high category.